AB0704 PRESCRIBING PRACTICES IN AXIAL SPONDYLOARTHROPATHY. (13th June 2020) - Maguire, S.; Gallagher, P.; O'shea, F. B.
Abstract : Background: Axial spondyloarthropathy(axSpA) treatment has undergone a number of significant developments over the past number of decades. Previously limited to non-steroidal anti-inflammatories (NSAIDs) and corticosteroids, treatment options now include synthetic disease modifying anti-rheumatic drugs(sDMARDs) and biologic agents. The development of national registries for inflammatory arthritis provides an opportunity to study medication usage in a large cohort of patients with axSpA. The Ankylosing Spondylitis Registry of Ireland (ASRI) is a source of epidemiological data on patients with axSpA in Ireland. The aim of this study was to examine medication exposure and outcomes. Objectives: To characterize a large cohort of patients with axSpA in terms of medications usage, burden of disease and patient reported outcomes. Methods: The patient population registered in the ASRI was analysed using IBM SPSS version 26. Patients were analyzed on the basis of medication exposure. The four treatment groups were classified as no treatment, NSAIDs only, biologics only, or biologics and NSAIDs. Mean age, duration of disease and delay to diagnosis was compared between groups. Burden of disease was assessed via mean BASDAI, BASFI, BASMI, HAQ and ASQoL between the four groups. Differences between groups was tested for statistical significance a one-way analysis of variance (ANOVA). A chi-squared test for independence was used to compare differences in rates of HLA-B27 positivity rates and gender. Results were deemed significant where p < 0.05. Results: At present 860 patients are currently enrolled in the ASRI with 76.6% (659) males and 23.4% (201) females. Average age of patients is 45.8 years, mean disease duration of 19.4 years with 95.5% (821) of patients listed as Caucasian. Mean scores were BASDAI 4.02, BASFI 3.7, BASMI 4.02, HAQ 0.55, and ASQoL of 6.51. Treatment groups were made up of 9.9%(85) on no treatment, 22.2%(191) NSAIDs treatment only, 34.8%(299) biologics treatment only and 32.1%(276) treated with both NSAIDs and biologics. Patients only on NSAIDs were noted to be older than patients on biologics, and those on both biologics and NSAIDs (p=0.02). Patients on NSAIDs were older at symptom onset than those on both biologic and NSAID treatment (p=0.02), however the effect size is small(0.012). No significant difference was noted between groups regarding disease duration, delay to diagnosis or distribution between genders (table 1). Difference in BASDAI scores between groups was significant between all groups, with patients on both biologics and NSAIDs having the highest scores and those on no treatment with the lowest scores(4.74 vs 3.37) possibly a reflection of disease severity(table 2). Conclusion: A large proportion of patients in the ASRI were treated with either biologics only or both biologics and NSAIDs. No treatment was the least common treatment within this cohort. Patients not on treatment tended to be older than those on any type of treatment. Overall patients on biologics alone tended to have better patient reported outcomes as compared to all other treatment groups. The development of longitudinal data for the ASRI will help to further understand the reason behind these differences. Disclosure of Interests: Sinead Maguire Grant/research support from: ASRI is supported by funding from Pfizer, AbbVie and UCB, Phil Gallagher: None declared, Finbar Barry O'Shea Grant/research support from: ASRI is supported by funding from Pfizer, AbbVie and UCB